Middle East and North Africa Economic Monitor, April 2016 : Syria, Reconstruction for Peace - Devarajan, Shantayanan (Washington, DC: World Bank, 2016)
The short term economic outlook for the Middle East and North Africa (MENA) region remains “cautiously pessimistic”. A combination of civil wars and refugee inflows, terrorist attacks, cheap oil, and subdued global economic recovery is expected to keep average growth in the MENA region around 3 percent in 2016, for the fourth year in a row. Furthermore, the humanitarian and economic situation in the war torn countries keep deteriorating. In this report we will explore ways in which a strategy of reconstruction of Syria—the most war-ravaged country in the region—could help foster a sustainable peace. This report argues that the impact of the civil war on the Syrian society will be persistent, and the challenges facing the country need to be addressed now. The report calls for the international community to be the guarantor of an inclusive reconstruction strategy that not only makes peace sustainable tomorrow, but makes it happen today: peace and reconstruction are two sides of the same coin.